KONSULTASI PUBLIK KEGIATAN PEMBANGUNAN DAN PENGEMBANGAN RUMAH SAKIT UMUM DAERAH - Nita Marikena (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
Public consultation is an activity that must be carried out by the person in charge of the business and/or activity who is obligated to prepare the Amdal document as contained in the Government Regulation of the Republic of Indonesia Number 22 of 2021 corcerning the Implementation of Environmental Protection and Management as a derivate of Article 22 and Article 185 letter b of the Law Republic of Indonesia Number 11 of 2020 concerning Job Creation. Rantauprapat Regional General Hospital is a hospital with class B classification of Non-Education which is planned to be built and developed which is located on an area of 24.553 m2 and a building area of 50.832,91 m2 based on the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 4 of 2021 mandatory prepare a Document of Environmental Impact Analysis (AMDAL). The public consultation was conducted using the seminar method and filling out a questionnaire. Based on the results of filling out the quistionnaire, there were 28,46% of respondents strongly agree, 70,00% agreed and 1,54% did not agree with the activity plan and there were 21,53% of respondents who said they were worried about the development plan. Keywords: Public consultation, Amda